2021
DOI: 10.51821/84.4.006
|View full text |Cite
|
Sign up to set email alerts
|

Is Cholecystectomy a cause of difficult biliary cannulation in endoscopic retrograde cholangiopancreatography?

Abstract: Background and study aim: In European Society of Gastrointestinal Endoscopy guidelines, biliary cannulation of naive papillae is defined as difficult in the presence of more than 5 papilla contacts, more than 5min cannulation time or more than one unintended pancreatic duct cannulation or opacification. It is not known whether cholecystectomy is a cause of difficult biliary cannulation. This study aimed to investigate whether cholecystectomy (CCY) is a cause of difficult biliary cannulation in patients who hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Conversely, one recent study conducted by Cankurtaran et al. revealed that a history of cholecystectomy was significantly associated with difficult cannulation (OR 2.014, p = 0.008) [ 19 ]. Another study has shown that ERCP difficulty increases in patients with a history of complicated cholecystectomy [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, one recent study conducted by Cankurtaran et al. revealed that a history of cholecystectomy was significantly associated with difficult cannulation (OR 2.014, p = 0.008) [ 19 ]. Another study has shown that ERCP difficulty increases in patients with a history of complicated cholecystectomy [ 35 ].…”
Section: Discussionmentioning
confidence: 99%